ESTIMATION OF ANNUAL RUNOFF AND PEAK FLOW AT NAZANIN CATCHMENT IN ERBIL, KURDISTAN REGION USING DIFFERENT APPROACHES - Aziz, Yaseen (Iraqi Geological Journal, 2020)
Runoff is excess rainfall or a portion of rainfall that flows over the watershed. In un-gauged streams, due to lack of data, many methods are used for runoff estimation. In this paper annual runoff and peak flow of Nazanin watershed were estimated at Nazanin Dam location using different methods. Soil Conservation Service (SCS) method, basin relation, (Hydrologic Engineering Center – Hydrologic Modeling System) HEC-HMS and Hydrologic engineering center (HEC-1) models were provided. The Watershed Modeling System (WMS) package was used for watershed delineation and computation of curve number. The area of Nazanin catchment is 72.14 km2, and the composite curve number is 81.3. The results of average annual rainfall estimated using the basin relationship method are more than that obtained from SCS method. The results of peak flood discharge for different return periods using different approaches such as SCS method, HEC-HMS and HEC-1 models are very close. But the results of basin relation are lower than SCS method. From the results of comparison, it was observed that HEC-HMS and HEC-1 models can be used for generation flood hydrograph at ungagged watershed.